2017
DOI: 10.1371/journal.ppat.1006374
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of miR-122-independent propagation of HCV

Abstract: miR-122, a liver-specific microRNA, is one of the determinants for liver tropism of hepatitis C virus (HCV) infection. Although miR-122 is required for efficient propagation of HCV, we have previously shown that HCV replicates at a low rate in miR-122-deficient cells, suggesting that HCV-RNA is capable of propagating in an miR-122-independent manner. We herein investigated the roles of miR-122 in both the replication of HCV-RNA and the production of infectious particles by using miR-122-knockout Huh7 (Huh7-122… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(60 citation statements)
references
References 66 publications
1
59
0
Order By: Relevance
“…miR-6880-5p was identified as a genotype 1b specific non-miR-122 type miRNA (S6A Fig). To examine the enhancement of replication of genotype 1b HCV by miRNAs, 751-122KO cells transfected with mimics of miRNAs (S6A and S6B Figs) were infected with chimeric HCV of genotype 1b Con1 strain and genotype 2a JFH1 strain (Con1C3/JFH) [23]. Among the miRNAs we examined, transfection of mimics of miR-504-3p and miR-574-5p exhibited slight but significant enhancement of replication of the chimeric HCV compared to control mimics, in contrast to large enhancement by that of miR-122 (S6C Fig).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…miR-6880-5p was identified as a genotype 1b specific non-miR-122 type miRNA (S6A Fig). To examine the enhancement of replication of genotype 1b HCV by miRNAs, 751-122KO cells transfected with mimics of miRNAs (S6A and S6B Figs) were infected with chimeric HCV of genotype 1b Con1 strain and genotype 2a JFH1 strain (Con1C3/JFH) [23]. Among the miRNAs we examined, transfection of mimics of miR-504-3p and miR-574-5p exhibited slight but significant enhancement of replication of the chimeric HCV compared to control mimics, in contrast to large enhancement by that of miR-122 (S6C Fig).…”
Section: Resultsmentioning
confidence: 99%
“…For a rapid identification of 5’UTR sequence of HCV, RNAs extracted from 100 µl of virus-containing supernatants or PBMCs were amplified by using a PrimeScript ® RT reagent Kit (Perfect Real Time) (Takara Bio) and 5’RACE was performed by using a 5’RACE System for Rapid Amplification of cDNA Ends, Version 2.0 (Life Technologies) as described by Ono et al [23].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Curiously, the C3U mutation has not been observed during selection experiments in cultured cells [17, 24, 25] and no naturally occurring C3U HCV genotypes have been deposited into Gene bank. Ono et al observed a viral G28A mutation that arose in the serum and peripheral blood monocytes of type 2-infected patients [25], however, the C3U variant has only been observed in patient serum after several weeks in anti-miR treatment, and only transiently. Whether the extrahepatic C3U genomes reflect growth of the C3U variant in the liver of re-bounding patients is not known, because liver biopsies are not available.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a growing body of evidence has demonstrated that miRNAs can play a key role in the regulation of viral replication. For example, the liver-specific miR-122 interacts with the 5′-UTR of the genome of the hepatitis C virus (HCV) and increases viral replication [12]. The H1N1 influenza A virus-induced miR-323, miR-491, and miR-654 inhibit viral replication by directly binding to the PB1 gene [13].…”
Section: Introductionmentioning
confidence: 99%